![SearchIcon](https://vmkt.vedantu.com/vmkt/PROD/png/bdcdbbd8-08a7-4688-98e6-4aa54e5e0800-1733305962725-4102606384256179.png)
A, B and C represents switches in ‘on’ position and A’, B’ and C’ represents them in ‘off’ position. Construct a switching circuit representing the polynomial $ABC + AB'C + A'B'C$. Using Boolean algebra, prove that the given polynomial can be simplified to $C\left( {A + B'} \right)$. Construct an equivalent switching circuit.
Answer
507.6k+ views
Hint: Use the property of Boolean algebra which are $A.A = A,{\text{ }}A.A' = 0,{\text{ }}A\left( {1 + B'} \right) = A,{\text{ & }}\left( {A + A'} \right) = 1$ for solving this problem.
Complete step-by-step answer:
Given polynomial is $ABC + AB'C + A'B'C$ switching circuit representing the given polynomial is shown in figure (1), where A, B and C represents switches in ‘on’ position and A’, B’ and C’ represents them in ‘off’ position
Now we have to prove that
$ABC + AB'C + A'B'C = C\left( {A + B'} \right)$
Consider L.H.S
$ABC + AB'C + A'B'C$
Take AC common from first two terms
$ \Rightarrow AC\left( {B + B'} \right) + A'B'C$
As we know in Boolean algebra value of $\left( {B + B'} \right)$ is equal to one
$ \Rightarrow AC\left( {B + B'} \right) + A'B'C = AC + A'B'C$
Now take C as common
$ \Rightarrow AC + A'B'C$ = $C\left( {A + A'B'} \right).............\left( 1 \right)$
Now $\left( {A + A'B'} \right)$ is written as$\left( {A + A'} \right)\left( {A + B'} \right)$, property of Boolean algebra.
Because we know in Boolean algebra the value of $A.A = A,{\text{ }}A.A' = 0,{\text{ & }}A\left( {1 + B'} \right) = A$
So,
$
\left( {A + A'} \right)\left( {A + B'} \right) = A.A + A.B' + A.A' + A'B' \\
= A + AB' + 0 + A'B' \\
= A\left( {1 + B'} \right) + A'B' = A + A'B' \\
$
Therefore
$\left( {A + A'B'} \right) = \left( {A + A'} \right)\left( {A + B'} \right)$
Therefore from equation (1)
$ \Rightarrow ABC + AB'C + A'B'C = C\left( {A + A'B'} \right) = C\left( {A + A'} \right)\left( {A + B'} \right)$
Now as we know in Boolean algebra value of $\left( {A + A'} \right)$ is equal to one
$ \Rightarrow ABC + AB'C + A'B'C = C\left( {A + B'} \right)$
=R.H.S
Hence Proved.
And the equivalent representation is shown in figure (2), where A, B and C represents switches in ‘on’ position and A’, B’ and C’ represents them in ‘off’ position.
Note: Whenever we face such types of questions always remember some of the basic properties of the Boolean algebra which is stated above then using these properties simplify the given polynomial, we will get the required answer.
Complete step-by-step answer:
Given polynomial is $ABC + AB'C + A'B'C$ switching circuit representing the given polynomial is shown in figure (1), where A, B and C represents switches in ‘on’ position and A’, B’ and C’ represents them in ‘off’ position
![seo images](https://www.vedantu.com/question-sets/38372eb2-8ff7-4fbd-89ee-809304a133741339685615612231783.png)
Now we have to prove that
$ABC + AB'C + A'B'C = C\left( {A + B'} \right)$
Consider L.H.S
$ABC + AB'C + A'B'C$
Take AC common from first two terms
$ \Rightarrow AC\left( {B + B'} \right) + A'B'C$
As we know in Boolean algebra value of $\left( {B + B'} \right)$ is equal to one
$ \Rightarrow AC\left( {B + B'} \right) + A'B'C = AC + A'B'C$
Now take C as common
$ \Rightarrow AC + A'B'C$ = $C\left( {A + A'B'} \right).............\left( 1 \right)$
Now $\left( {A + A'B'} \right)$ is written as$\left( {A + A'} \right)\left( {A + B'} \right)$, property of Boolean algebra.
Because we know in Boolean algebra the value of $A.A = A,{\text{ }}A.A' = 0,{\text{ & }}A\left( {1 + B'} \right) = A$
So,
$
\left( {A + A'} \right)\left( {A + B'} \right) = A.A + A.B' + A.A' + A'B' \\
= A + AB' + 0 + A'B' \\
= A\left( {1 + B'} \right) + A'B' = A + A'B' \\
$
Therefore
$\left( {A + A'B'} \right) = \left( {A + A'} \right)\left( {A + B'} \right)$
Therefore from equation (1)
$ \Rightarrow ABC + AB'C + A'B'C = C\left( {A + A'B'} \right) = C\left( {A + A'} \right)\left( {A + B'} \right)$
Now as we know in Boolean algebra value of $\left( {A + A'} \right)$ is equal to one
$ \Rightarrow ABC + AB'C + A'B'C = C\left( {A + B'} \right)$
=R.H.S
Hence Proved.
And the equivalent representation is shown in figure (2), where A, B and C represents switches in ‘on’ position and A’, B’ and C’ represents them in ‘off’ position.
Note: Whenever we face such types of questions always remember some of the basic properties of the Boolean algebra which is stated above then using these properties simplify the given polynomial, we will get the required answer.
Recently Updated Pages
Master Class 11 Economics: Engaging Questions & Answers for Success
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Master Class 11 Business Studies: Engaging Questions & Answers for Success
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Master Class 11 English: Engaging Questions & Answers for Success
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Master Class 11 Computer Science: Engaging Questions & Answers for Success
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Master Class 11 Accountancy: Engaging Questions & Answers for Success
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Master Class 11 Maths: Engaging Questions & Answers for Success
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Trending doubts
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
What organs are located on the left side of your body class 11 biology CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
How many valence electrons does nitrogen have class 11 chemistry CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Soap bubble appears coloured due to the phenomenon class 11 physics CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
How is the brain protected from injury and shock class 11 biology CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)
Define least count of vernier callipers How do you class 11 physics CBSE
![arrow-right](/cdn/images/seo-templates/arrow-right.png)